Fernando VII: impulso y freno a la sublevación de los españoles contra Napoleón - Emilio La Parra López (Casa de Velázquez, 2008)
In April 1808 the tension between the Spanish people and the French authorities was very high as a result of Napoleon’s refusal to recognise Fernando VII as king of Spain, the presence of French troops and the policy followed by Murat. The populace reacted in various different cities; however, their actions were directed not against the foreign occupier but against the announced return of Carlos IV to the throne. The channelling of popular protests in this direction and the absence of an uprising against Napoleon at a juncture which on the face of it appeared favourable to one was above all fruit of the machinations of Fernando VII and his closest advisors, who calculated that any action against the French would be detrimental to their main objective, namely the consolidation of Fernando VII’s position on the throne. When the uprising against Napoleon did take place in late May 1808, neither Fernando VII nor his closest advisors were in a position to intervene in Spanish affairs.